2018
DOI: 10.14710/parole.v6i2.27-40
|View full text |Cite
|
Sign up to set email alerts
|

Generic Structure and Cohesive Devices: A Study on the Final Project Report Presentation of the Accounting Students of Polines Semarang

Abstract: This study examines the generic structure and cohesive devices in the Final Project Report (FPR) presentation delivered in English by the Accounting students of Polines. Fourteen randomly selected subjects (10% of the third graders’ population) were involved and audio-recorded during their presentation. The recordings were then transcribed and analyzed using a descriptive-interpretative method. The result shows that the generic structure most presenters used was Greeting and Salutation–Self Introduction–Topic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…In Move 3 -Conclusion, there are two steps with a typical pattern as obligatory, M3SA -Summarizing the points/conclusion and M3SD -Thanking/thank you. The findings in previous research from Raharjo and Nirmala (2016) revealed that most presenters developed their presentations using a summary/conclusion. The steps above are categorized as obligatory because they have appeared 30 times with a percentage of 100%.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In Move 3 -Conclusion, there are two steps with a typical pattern as obligatory, M3SA -Summarizing the points/conclusion and M3SD -Thanking/thank you. The findings in previous research from Raharjo and Nirmala (2016) revealed that most presenters developed their presentations using a summary/conclusion. The steps above are categorized as obligatory because they have appeared 30 times with a percentage of 100%.…”
Section: Discussionmentioning
confidence: 90%
“…Then, the recorded video of the presentation was analyzed by the researcher. The researcher will analyze the pattern of the rhetorical structure found in the video presentation by using the adapted model by Singh and Ali (2019), Raharjo andNirmala (2016), andSeliman (1996). Following that, each piece of evidence will be further detailed and examined in light of the theories covered in the preceding chapter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raharjo & Nirmala (2018) looked at the generic structure and cohesive devices in accounting students' final project report presentations [12]. Referents and conjunctions are shown to be the most common grammatical cohesion devices utilized by accounting major students.…”
Section: B Review Of Previous Studiesmentioning
confidence: 99%
“…John Swales's (1990) rhetorically-based approach to genre and his Move Structure Theory to investigate the genre-based discourse structure of academic journal articles opened up new perspectives in the field, and inspired research related to various written academic genres internationally (Anthony, 1999;Atai and Habibi, 2009;Bunton, 2005;Golebiowski, 1999;Holmes, 1997;Tardy, 2011;Zand-Vakill and Kashani, 2012), and in Hungary, too (Árvay and Tankó, 2004;Doró, 2013aDoró, , 2013b. At the same time, interest in the move structure analysis of oral academic genres has only intensified in the last decade focusing, for instance, on TED talks (Chang and Huang, 2015; Li and Li, 2021; Miranda and Moritz, 2021; Poonpon and Kraisriwattana, 2020; Ratanakul, 2017) and AOPs (Ädel, 2023; Chang and Huang, 2015; Hu and Liu, 2018; Singh and Ali, 2019; Raharjo and Nirmala, 2016).…”
Section: Introductionmentioning
confidence: 99%